Fabrication and characterization of inorganic/organic thin film junction for photovoltaic applications - Alaei, Iraj (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
This work concerns the adaption of paint coating technique for TiO2 thin films and solution cast technique for PEO. The main objective of this research is to study the possibility of developing two configurations photovoltaic junction including ITO/TiO2/PEO/ITO and ITO/TiO2-Dye/PEO/ITO. TiO2 prepared in a form of paste and painted on ITO glass with different thickness. The polymer solution blending working electrode prepared by polyethylene oxide, chitosan, NH4I and a 2-3 crystals of I2. The ITO/TiO2 samples are characterized by X-ray diffraction (XRD), Scanning electron microscope (SEM) and UV-Visible spectroscopy. XRD revealed nanocrystalline TiO2 with particle size of 23.8nm. SEM shows a range of thickness of 11.5-18.5 μm and surface morphology. UV-Visible Spectroscopy shows the thinner layer of TiO2 thin film provide better absorption of light. The polymer shows higher conductivity at 45wt % NH4I with (1.18±0.7) ×10-5S cm-1. Some samples of TiO2 thin films soaked to the three selected dyes, which are Henna, Turmeric and Sumac over night for dye sensitized solar cell. Two configurations of ITO/TiO2/PEO/ITO and ITO/TiO2-Dye/PEO/ITO photovoltaic cells were assembled and characterize by I-V curve. PV cells of ITO/TiO2/PEO/ITO shows that one layer of TiO2 has a better PV performance through open circuit voltage (VOC), short circuit current (JSC)and fill factor at 350 mV, 2.5 μA/cm2, and 46% respectively. Cells of ITO/TiO2-Dye/PEO/ITO revealed that among three selected dyes, Sumac shows better performance in the cell through open circuit voltage (VOC), short circuit current (JSC), and fill factor at 394mV, 0.93 mA/cm2, and 41% respectively.